Towards a better understanding of the genus Sciurella Allman, 1883 (Cnidaria: Hydrozoa: Plumulariidae): evidence from an integrative study - Galea, Horia R.; Maggioni, Davide; Di Camillo, Cristina G. (Zootaxa, 2021)
The genus Sciurella Allman, 1883 is reassessed based on fertile specimens from Indonesia and Australia, using both morphological and genetic approaches. The genus is resurrected and kept distinct from Nemertesia Lamouroux, 1812 on the account of its long, tubular hydrothecae, and the gonothecae (of which only the female ones are known) provided with nematothecae. Stellate gonothecae correspond to S. indivisa Allman, 1883, while urn-shaped gonothecae are subjectively attributable to S. cylindrica (Kirchenpauer, 1876), comb. nov., a nominal species originally described based on sterile material. The taxonomy of the latter species is discussed in light of the available literature data, and Antennularia cylindrica Bale, 1884 is confidently assigned to its synonymy. Plumularia dolichotheca Allman, 1883 is provisionally transferred to Sciurella, as S. dolichotheca comb. nov., pending the discovery of fertile specimens and reliable evidence from molecular studies. The newly-generated genetic data for S. indivisa and S. cylindrica clearly confirm the distinction between Sciurella and Nemertesia, the two genera occupying divergent positions within the Plumulariidae phylogenetic hypotheses.